2010
DOI: 10.1016/j.ajhg.2010.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for a Missense Mutation in SERPINH1, which Encodes the Collagen Chaperone Protein HSP47, Results in Severe Recessive Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta (OI) is characterized by bone fragility and fractures that may be accompanied by bone deformity, dentinogenesis imperfecta, short stature, and shortened life span. About 90% of individuals with OI have dominant mutations in the type I collagen genes COL1A1 and COL1A2. Recessive forms of OI resulting from mutations in collagen-modifying enzymes and chaperones CRTAP, LEPRE1, PPIB, and FKBP10 have recently been identified. We have identified an autosomal-recessive missense mutation (c.233T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(235 citation statements)
references
References 23 publications
4
225
1
5
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] On the contrary, here 15/32 families with no mutation in collagen I had a typical type I phenotype, and 25 additional families were excluded on the basis of a negative sequencing result in combination with an unclear clinical phenotype. These individuals may have a COL1A1 null allele caused by a non-exonic mutation missed here; however, another OI-related gene might be causative in some instances.…”
Section: Noteworthy Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] On the contrary, here 15/32 families with no mutation in collagen I had a typical type I phenotype, and 25 additional families were excluded on the basis of a negative sequencing result in combination with an unclear clinical phenotype. These individuals may have a COL1A1 null allele caused by a non-exonic mutation missed here; however, another OI-related gene might be causative in some instances.…”
Section: Noteworthy Mutationsmentioning
confidence: 99%
“…Dominant mutations in collagen type I are generally stated to be responsible for 90% of cases, while a plethora of other genes have been associated with non-collagen OI in recent years. [1][2][3][4][5][6][7][8][9][10][11][12][13] Collagen type I, encoded by COL1A1 and COL1A2, constitutes 85% of the organic matrix in skeletal tissue, and forms a framework for mineral deposition, rendering bone the tensile properties needed to withstand torsion and bending powers. Procollagen is a heterotrimer, with a helical 1014-amino acid-long central stretch of two α1-and one α2-chains, which is flanked by globular N-and C-terminal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Only four different homozygous SERPINH1 missense mutations have been described, one in Dachshunds and three in humans, all resulting in moderate to severe osteogenesis imperfecta 67 (TABLE 1). These mutations are located in the serine type endopeptidase inhibitor domain of serpin H1, which is crucial for chaperone func tion, leading to intracellular retention of type I collagen.…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…In addition to a suite of osteogenic targets osx/sp7, bglap, sparc/osteonectin, and col10a1, TCDD exposure attenuates expression of FKBP10 and SERPINH1, genes associated with posttranslational modification and transport of collagens that comprise bone ECM. In combination with OSX/ SP7, mutations in both FKBP10 and SERPINH1 are linked to severe osteogenesis imperfecta (Alanay et al, 2010;Christiansen et al, 2010), which offers further support for the bone phenotype we observed in TCDD-treated medaka.…”
Section: Figmentioning
confidence: 60%